A new 3-arylbenzofuran derivative EIE-2 reestablishes Treg-dependent tolerance in rheumatoid arthritis by targeting on Syk induced mTOR and PKCθ imbalance - Li, Ping; Yin, Xin; Wen, Xinzhu; Li, Xuyu; Wang, Yuqing; Zhan, Hongyan; Che, Hanqing; Yao, Chunsuo; Hou, Qi; Zhang, Ziqian; Zheng, Ruifang; Lin, Mingbao (Frontiers in Immunology, 2025)
IntroductionDysfunctional self-tolerance is thought to play a crucial role in the onset of rheumatoid arthritis (RA) pathogenesis. Poorly functioning regulatory T cells (Tregs) lead to extreme situations where self-tolerance is robustly disrupted. However, there are many uncertainties regarding its immunosuppressive pathways, especially concerning therapeutic drugs that are still in their infancy. Therefore, deciphering potential targets and developing novel drugs to ameliorate functional Tregs deficiency appears to be an efficient therapeutic approach for controlling RA.MethodsThe therapeutic effects of EIE-2, a novel 3-arylbenzofuran derivative, were evaluated in collagen-induced arthritis (CIA) rats and carrageenan-induced paw edema mice in vivo, as well as in LPS-, PMA- or TNF-α-stimulated human CD4+ T cells (Jurkat), human synovial sarcoma cells (SW982) and primary isolated lymphocytes in vitro. The role of Syk in Treg-dependent tolerance and the mechanism of EIE-2 were explored using western blotting, quantitative reverse transcription PCR (qRT-PCR) and flow cytometry. Potential mechanistic targets were further validated through siRNA knockdown and molecular docking analysis.ResultsEIE-2 significantly ameliorated arthritic symptoms and pathological damage in CIA rats by reducing pro-inflammatory cytokines and increasing anti-inflammatory factors in synovium and serum, and exhibited similar therapeutic effects in carrageenan-induced pedal edema mice. Moreover, EIE-2 potently suppressed the inflammatory responses in human synoviocyte SW982 cells, primary isolated lymphocytes and CD4+ Jurkat cells. Its therapeutic potential was associated with upregulation of Tregs during the active phase and downregulation during the inactive phase of RA. Mechanistically, EIE-2 modulated the PKCθ/mTOR ratio via Syk targeting, thereby restoring homeostasis in Tregs.DiscussionEIE-2 is a potential therapeutic candidate for RA. The underlying mechanism may involve its targeting on Syk to upregulate the PKCθ/mTOR ratio during the active phase of RA and downregulate the PKCθ/mTOR ratio during the inactive phase of RA, ultimately promoting Treg-dependent tolerance restoration.